Approaching Equity in Consumer Health Information Delivery: Net Wellness - Morris, Theodore A. (American Medical Informatics Association, 1997)
The growing public interest in health and wellness information stems from many sources, including social changes related to consumers' rights and women's health movements, and economic changes brought about by the managed health care revolution. Public, hospital, and medical center libraries have been ill-equipped to meet the increasing need for consumer-oriented materials, even though a few notable programs have been established. The “Information Superhighway” could be an effective tool for sharing health information if access to telecomputing equipment and training were available to those with an information need. The University of Cincinnati Medical Center, with its libraries in the leading role, is delivering NetWellness, an electronic consumer health library service, to residents of 29 counties in three midwestern states. Users connect directly through the Internet, through regional Free-Nets, and by visiting one of 43 public access sites where networked workstations have been installed. The continued success of the project depends on developing partnerships, providing quality content and maintaining fair access.